Could green infrastructure supplement ecosystem service provision from semi-natural grasslands?. (15th February 2023) - Hooftman, Danny A.P.; Kimberley, Adam; Cousins, Sara A.O.; Santamaría Bueno, Silvia; Honnay, Olivier; Krickl, Patricia; Plue, Jan; Poschlod, Peter; Traveset, Anna; Bullock, James M.
Abstract: Ancient semi-natural grasslands in Europe are important for ecosystem service (ES) provision. Often, the surrounding matrix contains 'Grassland Green Infrastructure' (GGI) that contain grassland species which have the potential to supplement grassland ES provision across the landscape. Here we investigate the potential for GGI to deliver a set of complementary ES, driven by plant composition.We surveyed 36 landscapes across three European countries comprising core grasslands and their surrounding GGI. We calculated community-level values of plant species characteristics to provide indicators for four ES: nature conservation value, pollination, carbon storage and aesthetic appeal.Inferred ES delivery for GGI was substantially lower than in core grasslands for conservation, pollination and aesthetic appeal indicators, but not for carbon storage. These differences were driven by the GGI having 17% fewer plant species, and compositional differences, with 61% of species unique to the core grasslands. In addition, connectivity to the core, the amount of GGI and inferred seed dispersal distances by livestock, were strongly positively correlated with conservation value, pollination and aesthetic indicators. All ES indicators showed similar responses to the GGI spatial structure and distance to the core, suggesting robust effects of these drivers on ES. We projected that improved landscape-wide delivery of nature conservation value and pollination could be achieved through targeted GGI management. Reductions in the distances seeds would need to disperse, more GGI, along with a diversification of the GGI elements, were predicted to enhance service credits.We conclude that for vegetation-related ES, species surveys can be employed to assess potential ES delivery. Creating and enhancing GGI is a useful landscape management strategy to supplement the ES delivered by ancient grasslands. Highlights: Green Infrastructure (GI) has great potential to provide environmental benefits. The actual value of GI for Ecosystem Services (ES) provision is rarely assessed. We find GI has the potential to provide ES in grassland landscapes in 3 countries. GI value is constrained by dissimilarity and poor connectivity to core grasslands. Enhancing dispersal and improving the GI habitat could provide a future ES credit.